طرق محاكاة دارة عمل محرّك الاحتراق الداخلي بهدف تطويره - غدير نبيل (Latakia University Journal -Engineering Sciences Series, 2019)
تلعب عملية محاكاة ونمذجة دارة عمل محرك الاحتراق الداخلي دوراً كبيراً في تطوير المحركات, وتحسين مواصفاتها وأدائها, وملاءمتها لشروط التشغيل المختلفة . وهي توفر جهداً تجريبياً كبيراً رغم أنها لا تغني عنه ، فهي تشكل الخطوة الأولى لمهندس التصميم والتطوير, للتحقق من مواصفات المحرك الجديد وأدائه بأقصر وقت ممكن . يبين البحث كيفية إجراء محاكاة دارة عمل محرك رباعي الأشواط ذي أربع أسطوانات, مع تشحين عنفي ، وتظهر النتائج تأثر أداء المحرك بتغير ظروف التشغيل . فقد أمكن ,عن طريق المحاكاة وباستخدام الحاسب ,حساب منحني انتقال الحرارة من حجرة الاحتراق إلى الجدران الداخلية للأسطوانة حسب قوشني, وكذلك منحني معدل إطلاق الحرارة إضافة إلى تحديد تأثير لحظة بداية الاحتراق في كلٍّ من المردود الحراري الدليلي ,ودرجة حرارة غازات العادم ,والضغط الأعظمي داخل الاسطوانة, وكذلك تأثير فترة تطابق الصمامات في الاستهلاك النوعي الفعلي للوقود ,وللهواء ,وفي نسبة الهواء للوقود ,وفي تغير درجة حرارة غازات العادم . The Simulation of Internal Combustion Engine Cycle plays a big role in developing engines and adapting them to different working conditions. This method spares a lot of experiments, but it is not enough alone. Also, it is the first step for the engine development engineer to test the performance of the new engine quickly. This paper deals with the Simulation of the cycle of a four-stroke engine with four cylinders using turbocharger. The results show the influence of operation condition on the engine performance. Heat release curve and heat transfer from working gas to cylinder walls were calculated. In addition, the influence of start of Combustion on engine Operation; thermal efficiency (); exhaust gas temperature (Tex) and maximum cylinder pressure () were indicated. Also the paper shows the effect of valve overlap period on the specific consumption of fuel and air (,); air-fuel equivalence ratio (l) and exhaust gas temperature change ().